2014
DOI: 10.1177/0146167214533130
|View full text |Cite
|
Sign up to set email alerts
|

Get the Message

Abstract: Results from three studies demonstrate that victims' justice-related satisfaction with punishment is influenced by the kind of feedback they receive from offenders after punishment. In contrast to previous studies that found a discrepancy between anticipated and experienced satisfaction from punishment (Carlsmith, Wilson, & Gilbert, 2008), participants were able to accurately predict their satisfaction when made aware of the presence or absence of offender feedback acknowledging the victim's intent to punish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 49 publications
(84 reference statements)
6
57
0
1
Order By: Relevance
“…When we talk about "satisfaction," we mean a psychological state in which the victim/avenger experiences (a) a sense of justice achieved (i.e., that everybody got what they deserved), (b) psychological closure (i.e., that s/he can now put up with what had happened and "move on"), and (c) positive affect (e.g., satisfaction, relief, pleasure). Previous research on the hedonic benefits of taking revenge has shown that these three facets are strongly correlated with each other (e.g., Funk et al, 2014;Gollwitzer et al, 2011;Sjöström & Gollwitzer, 2015), which is why they are usually combined into a single measure of "justicerelated satisfaction." It should be noted that previous research had used different sets of items in different studies, with more comprehensive scales yielding higher internal consistencies (e.g., 12 items in Funk et al, 2014; Studies 1 and 2b) than shorter scales (as in Gollwitzer et al, 2011or Funk et al, 2014Study 2a), which sometimes yielded internal consistencies (i.e., Cronbach's alphas) around .60 (e.g., Sjöström & Gollwitzer, 2015; Study 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When we talk about "satisfaction," we mean a psychological state in which the victim/avenger experiences (a) a sense of justice achieved (i.e., that everybody got what they deserved), (b) psychological closure (i.e., that s/he can now put up with what had happened and "move on"), and (c) positive affect (e.g., satisfaction, relief, pleasure). Previous research on the hedonic benefits of taking revenge has shown that these three facets are strongly correlated with each other (e.g., Funk et al, 2014;Gollwitzer et al, 2011;Sjöström & Gollwitzer, 2015), which is why they are usually combined into a single measure of "justicerelated satisfaction." It should be noted that previous research had used different sets of items in different studies, with more comprehensive scales yielding higher internal consistencies (e.g., 12 items in Funk et al, 2014; Studies 1 and 2b) than shorter scales (as in Gollwitzer et al, 2011or Funk et al, 2014Study 2a), which sometimes yielded internal consistencies (i.e., Cronbach's alphas) around .60 (e.g., Sjöström & Gollwitzer, 2015; Study 3).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the message hypothesis. In order to alleviate recurring problems of low revenge rates in previous laboratory studies on revenge (see Funk et al, 2014;Gollwitzer et al, 2011), we used a false feedback procedure on participants' vengeful desires. Although participants did not openly express skepticism toward the validity of this procedure, participants' agreement with the result of the bogus punishment test was relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several reasons why revenge should be empowering. Revenge can teach offenders a lesson (Funk, McGeer, & Gollwitzer, 2014), and it can communicate that one will not put up with bad behaviour (e.g., Gollwitzer & Denzler, 2009;Gollwitzer, Meder, & Schmitt, 2011). Revenge can indicate strength and has therefore been associated with bolstered self-esteem following a transgression (Zdaniuk & Bobocel, 2012).…”
Section: Revengementioning
confidence: 99%